Geomorphology of Martel inlet, King George Island, Antarctica: a new interpretation based on multi-resolution topo-bathymetric data - PERONDI,CLEIVA (2022)
Abstract This study investigated the terrestrial and submarine geomorphology and glacial landform records in the Martel inlet (King George Island) using a multi-resolution topobathymetric data based on seismic, multibeam surveys and terrestrial satellite datasets (REMA DEM). Geomorphometric analysis provided glacial landforms and sedimentary processes interpretation. The submarine sector has a mean depth of 143 m, a maximum depth of 398 m, and most of it has a low slope (0°–16°). Steep slopes (>30°) are found along the mid-outer sectors transition area. The continental shelf was divided into inner fjord (49 m depth), middle fjord (119 m), and outer fjord (259 m), based on depth, elevation and slope. The topobathymetric digital model provides evidence of geomorphological contrasts between these zones in the fjord’s seafloor and subaerial environments. A prominent morainal bank in the transition between the inner and middle parts marks the limit of a past stationary stage of the Dobrowolski-Goetel ice margin. Streamlined glacial lineations demonstrate an NE-SW past ice flow direction and a wet-based thermal regime. The combined analysis of submarine and subaerial landforms enable the understanding of the former glacier configuration and its deglaciation history.